Comparing satellite based tidal resource assessment (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy offers significant potential as a sustainable and predictable renewable energy source. Accurate characterization of tidal resources is critical for identifying optimal sites and designing efficient energy conversion systems. In order to optimise the process of identifying regions with a high tidal energy potential as well as to provide data for studies on the global or regional potential of tidal energy, satellite data can play a significant role. Not only is it available for all regions around the globe, but also in a lot of forms it is available without any access restrictions. The research aims to assess the accuracy and reliability of the new code based on the satellite-derived AVISO model in diverse tidal environments, providing insights for improving tidal energy resource assessments. FES2014 and FES2022 build on analysis of sea surface height and velocity fields as collected by satellite imagery. The primary objective is to evaluate the performance of a satellite-data-driven tidal code in predicting key parameters, including tidal range, velocity profiles, and energy potential, by benchmarking its outputs for the North Atlantic. The results of the analysis are compared against ResourceCode, an online platform developed by the French Research Institute for Exploitation of the Sea (IFREMER) that provides tools, datasets, and models for marine research. ResourceCode is based on a simulation tool which considers bathymetry maps and various hydrodynamic parameters. This comparison aims to identify discrepancies, assess the suitability of the code for different environments, and propose improvements for enhanced precision in tidal resource characterization. In order to quantify potential deviations between the two bases, three different validation cases have been selected:A high flow velocity site in Raz BlanchardA high flow velocity site in Fall of Warness A tidal range site on the estuary of river MerseySpatial and temporal variability in tidal predictions were used to quantify the agreement between the two data sources.The preliminary results highlight small discrepancies between the new AVISO-based tidal code and the ResourceCode across the sites considered. Across the different locations, maximum tidal velocities presented a divergency lower than 5%. Similarly, the average tidal velocity and potential energy showed a decent agreement, resulting in a difference of 10% on average. These findings indicate strong performance of both codes in high-velocity tidal environments.This study demonstrates that while both the AVISO-based tidal code and the Resource code provide reliable estimates in high-velocity coastal regions, the new code overestimates the condition possibly for the missing interaction with wind. The AVISO-based code is a good option for an overview of the energy potential of a country and seeking possible locations. When ResorceCode is more accurate of detail location as among islands in an archipelago and temporal prediction. The discrepancies between the two codes leave room for improvement in the robustness of the AVISO-based code, where at the same time it can enable developers and suppliers in ocean energy sector to expand their market and define potential allocation outside of Europe.